2009
DOI: 10.4046/trd.2009.67.5.409
|View full text |Cite
|
Sign up to set email alerts
|

Community-Associated Methicillin-Resistant Staphylococcus aureus Colonization in the Upper Respiratory Tracts of Korean Military Recruits

Abstract: Background: Several large outbreaks have demonstrated the threat of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) in close-contact environments, such as occurs during training and quartering of military recruits training. In South Korea, which is a hospital or healthcare-associated MRSA prevalent area, military service is compulsory for all healthy young men. We surveyed and determined the extent of CA-MRSA colonization in the upper respiratory tracts of Korean military recruits. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since cultures are more likely to be performed in refractory infections or abscess-forming SSTI, MR rates in this study would be higher than the actual colonization rate of CA-MRSA. A previous epidemiologic study evaluating Korean military recruits from November 2004 to March 2005 reported 6.6% of CA-MRSA colonization rate, 16 and a follow-up study is required for the evaluation of current epidemiologic status. Third, although we followed a previously used definition of CA-MRSA, a certain portion of cases would be originated from OPD or primary care.…”
mentioning
confidence: 99%
“…Since cultures are more likely to be performed in refractory infections or abscess-forming SSTI, MR rates in this study would be higher than the actual colonization rate of CA-MRSA. A previous epidemiologic study evaluating Korean military recruits from November 2004 to March 2005 reported 6.6% of CA-MRSA colonization rate, 16 and a follow-up study is required for the evaluation of current epidemiologic status. Third, although we followed a previously used definition of CA-MRSA, a certain portion of cases would be originated from OPD or primary care.…”
mentioning
confidence: 99%